Demonstration of a signal enhanced fast Raman sensor for multi‐species gas analyses at a low pressure range for anesthesia monitoring. (27th May 2015) - Schlüter, Sebastian; Krischke, Frederick; Popovska‐Leipertz, Nadejda; Seeger, Thomas; Breuer, Georg; Jeleazcov, Christian; Schüttler, Jürgen; Leipertz, Alfred; Joubert, Pierre; Lavorel, Bruno; Kiefer, Johannes; Moger, Julian
<x xml:space="preserve">Abstract</x> The spontaneous Raman scattering technique is an excellent tool for a quantitative analysis of multi‐species gas mixtures. It is a noninvasive optical method for species identification and gas phase concentration measurement of Raman active molecules, since the intensity of the molecule specific Raman signal is linearly dependent on the concentration. Applying a continuous wave (cw) laser it typically takes a few seconds to capture a gas phase Raman spectrum at room temperature. Nevertheless in contrast to these advantages the weak Raman signal intensity is a major drawback. Thus, it is still challenging to detect gas phase Raman spectra in a low‐pressure regime with a temporal resolution of only a few 100 ms. In the presented study a fully functional gas phase Raman system for measurements in the low‐pressure regime (p ≥ 980 hPa (absolute)) is presented; it overcomes the drawback of the weak Raman effect by using a multipass cavity to enhance the Raman signal. The signal amplification of a retro‐reflecting cavity is experimentally compared to a near‐confocal cavity. A description of this sensor setup as well as of the calibration procedure, which also allows the quantification of condensable gases, is presented. Moreover the functionality of the sensor system is demonstrated in a measurement campaign at an anesthesia simulator under clinical relevant conditions and in comparison to a conventional gas monitor. Copyright © 2015 John Wiley & Sons, Ltd.